Aspetti di polemica antigiudaica nell'opera di Esichio di Gerusalemme (con particolare attenzione al "Commentario al Levitico") - Tampellini, Stefano (Annali di storia dell'esegesi, 1999)
The aspects of anti-Jewish polemic in the work of Hesychius of Jerusalem, in particular in his Commentary on Leviticus, are presented (a) to give us a picture of the Jews and Judaism in Hesychius, and (b) to seek out elements to help us reconstruct the historical background that provided the context for the polemic, thus allowing us to glimpse an ecclesiastical reality where room could be found for a literal interpretation of the Law and the observance of some of its precepts (e.g. food laws, and those relating to childbirth and contact with corps).